2009
DOI: 10.1080/15389580802493155
|View full text |Cite
|
Sign up to set email alerts
|

The Need for Enhanced Protocols for Assessing the Dynamic Performance of Booster Seats in Frontal Impacts

Abstract: Booster seats aim to achieve a good seat belt fit for children too small to use the adult seat belt. Variations in dynamic seat belt fit observed among these seventeen commercially available booster seats demonstrate the need for regulatory protocols that incorporate assessment of dynamic seat belt fit. With current technologies, visual examination of the seat belt during dynamic testing is the best method for assessing this performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Given the high DAB rate observed, it would appear the booster seats used in the Part 2 trials may not have been successful in improving the match between the child and the vehicle's seatbelt geometry for all children who participated in this study. Previous work has demonstrated that not all booster seats are successful in meeting their objective of optimizing seatbelt fit in test dummies (Brown et al 2009;Reed et al 2009). In Australia, the ability of a booster seat to provide good seatbelt positioning is now regulated through the Australian Standard and assessed in the Australian Child Restraint Evaluation Program.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high DAB rate observed, it would appear the booster seats used in the Part 2 trials may not have been successful in improving the match between the child and the vehicle's seatbelt geometry for all children who participated in this study. Previous work has demonstrated that not all booster seats are successful in meeting their objective of optimizing seatbelt fit in test dummies (Brown et al 2009;Reed et al 2009). In Australia, the ability of a booster seat to provide good seatbelt positioning is now regulated through the Australian Standard and assessed in the Australian Child Restraint Evaluation Program.…”
Section: Discussionmentioning
confidence: 99%